PEMIKIRAN PENDIDIKAN PESANTREN K.H. HASYIM ASY’ARI DAN PENGEMBANGAN PENDIDIKAN ISLAM DI INDONESIA - Abdul Hadi; Aries Abbas; Padjrin Padjrin; Munir Munir (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2021)
This study aims to discuss the thoughts of K.H. Hasyim Asy'ari about pesantren education and its relevance to Islamic education in Indonesia, including leadership, educational goals, and the character of students. K.H. Hasyim Asy'ari for 48 years leading the Tebuireng Islamic Boarding School has devoted a lot of his thoughts to improving the quality of the pesantren. Therefore, this study aims to discuss the thoughts of K.H. Hasyim Asy'ari about pesantren education and its relevance to Islamic education in Indonesia, including leadership, educational goals, and the character of students. This research is a library research with a qualitative approach. The data sources used are books about the biography of K.H. Hasyim Asy'ari and the website of the Tebuireng Islamic Boarding School. Then the data were analyzed through data reduction, data presentation, and drawing conclusions. Based on the results of the study that the educational thinking of K.H. Hasyim Asy'ari is relevant to the development of Islamic education in Indonesia. First, it is relevant to educational leadership in pesantren/madrasah, namely paternalistic and democratic leadership. Second, it is relevant to national education goals. Third, it is relevant to the 18 characters developed in schools today.